2020 32nd International Symposium on Power Semiconductor Devices and ICs (ISPSD) 2020
DOI: 10.1109/ispsd46842.2020.9170129
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Avalanche Free Super Junction-TCIGBT for High Power Density Operation

Abstract: This is a repository copy of Dynamic avalanche free super junction-TCIGBT for high power density operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In an IGBT, employing a p-pillar is a complex design challenge. In the trench Clustered IGBTs, where these p-pillars are only connected to the floating p well, an effective PMOS can be formed to extract holes in a very effective way, which can lead to a very significant reduction in turn-off energy losses from 7.2 mJ to 2.5 mJ, without affecting on-state losses, as shown in Fig 5 [7]. As TCIGBTs are devoid of limitations posed by the dynamic avalanche, our studies showed that such SJ-TCIGBTs can be operated at 500 A/cm^2 with significantly low switching losses and can operate beyond the 1-D material limits of SiC at 3 kV or so, as shown in Fig 6.…”
Section: In Conventionalmentioning
confidence: 99%
“…In an IGBT, employing a p-pillar is a complex design challenge. In the trench Clustered IGBTs, where these p-pillars are only connected to the floating p well, an effective PMOS can be formed to extract holes in a very effective way, which can lead to a very significant reduction in turn-off energy losses from 7.2 mJ to 2.5 mJ, without affecting on-state losses, as shown in Fig 5 [7]. As TCIGBTs are devoid of limitations posed by the dynamic avalanche, our studies showed that such SJ-TCIGBTs can be operated at 500 A/cm^2 with significantly low switching losses and can operate beyond the 1-D material limits of SiC at 3 kV or so, as shown in Fig 6.…”
Section: In Conventionalmentioning
confidence: 99%
“…This is because DA-free operation can enable reduction in the gate resistance, reducing switching losses and enhancing reliability. The Trench Clustered IGBT (TCIGBT) is the only DA-free solution that has been experimentally proven so far [7][8][9][10][11]. Its self-clamping feature and PMOS operation are effective in managing the peak electric field distribution beneath trench gates.…”
Section: Introductionmentioning
confidence: 99%